THE FUTURE OF DECENTRALIZED FINANCE (DEFI): DISRUPTING TRADITIONAL BANKING MODELS - Amir Raza; Roya Zahir (Journal Markcount Finance, 2026)
The rapid advancement of blockchain technology has given rise to Decentralized Finance (DeFi), a financial ecosystem that operates without traditional intermediaries and challenges the foundational structures of conventional banking. DeFi platforms enable peer-to-peer financial services through smart contracts, offering increased transparency, accessibility, and efficiency. This study aims to analyze the potential of DeFi to disrupt traditional banking models by examining its core mechanisms, value propositions, and structural differences from centralized financial institutions. The research seeks to assess both the opportunities and challenges posed by DeFi in reshaping financial intermediation. A qualitative analytical approach was employed, drawing on an integrative review of peer-reviewed literature, industry reports, and documented DeFi case examples. Data were analyzed through thematic synthesis to compare DeFi functionalities with traditional banking operations, focusing on governance, risk management, and financial inclusion. The findings indicate that DeFi introduces innovative financial models that reduce transaction costs, expand access to financial services, and enhance operational transparency. The study concludes that DeFi represents a transformative yet complementary force rather than a complete replacement for traditional banking. Its future impact will depend on regulatory adaptation, technological maturity, and institutional integration.